Night without End : The Fate of Jews in German-Occupied Poland - Engelking, Barbara, 1962-; Grabowski, Jan, 1962- (Book collections on Project MUSE., 2022)
"Three million Polish Jews were murdered in the Holocaust, wiping out nearly 98 percent of the Jewish population who had lived and thrived there for generations. Night Without End tells the stories of their resistance, suffering, and death in unflinching, horrific detail. Based on meticulous research from across Poland, it concludes that those who were responsible for so many deaths included a not insignificant number of Polish villagers and townspeople who aided the Germans in locating and slaughtering Jews. When these findings were first published in a Polish edition in 2018, a storm of protest and lawsuits erupted from holocaust deniers and from people who claimed the research was falsified and smeared the national character of the Polish people. Night Without End, translated and published for the first time in English in association with Yad Vashem, presents the critical facts, significant findings, and the unmistakable evidence of Polish collaboration in the genocide of Jews"--